The systemic pathology of cerebral malaria in African children - Milner, Danny A.; Whitten, Richard O.; Kamiza, Steve; Carr, Richard; Liomba, George; Dzamalala, Charles; Seydel, Karl B.; Molyneux, Malcolm E.; Taylor, Terrie E. (Frontiers in Cellular and Infection Microbiology, 2014)
Pediatric cerebral malaria carries a high mortality rate in sub-Saharan Africa. We present our systematic analysis of the descriptive and quantitative histopathology of all organs sampled from a series of 103 autopsies performed between 1996 and 2010 in Blantyre, Malawi on pediatric cerebral malaria patients and control patients (without coma, or without malaria infection) who were clinically well characterized prior to death. We found brain swelling in all cerebral malaria patients and the majority of controls. The histopathology in patients with sequestration of parasites in the brain demonstrated two patterns: a) the “classic” appearance (i.e., ring hemorrhages, dense sequestration, and extra-erythrocytic pigment) which was associated with evidence of systemic activation of coagulation and b) the “sequestration only” appearance associated with shorter duration of illness and higher total burden of parasites in all organs including the spleen. Sequestration of parasites was most intense in the gastrointestinal tract in all parasitemic patients (those with cerebral malarial and those without).